Popular culture in the age of white flight : fear and fantasy in suburban Los Angeles - Avila, Eric, 1968- (American crossroads, 2004)
Los Angeles pulsed with economic vitality and demographic growth in the decades following World War II. This vividly detailed cultural history of L.A. from 1940 to 1970 traces the rise of a new suburban consciousness adopted by a generation of migrants who abandoned older American cities for Southern California's booming urban region.